1995
DOI: 10.1590/s0100-83581995000100005
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da solarização do solo através de plástico transparente sobre o desenvolvimento da tiririca (Cyperus rotundus)

Abstract: RESUMOUm ensaio foi conduzido em condições de campo, durante o verão, com o objetivo de avaliar o potencial da técnica de solarização do solo no controle da tiririca (Cyperus rotundus L.). O delineamento experimental utilizado foi o de blocos casualizados com três repetições, e os tratamentos num esquema fatorial 2 X 2 X 3, sendo duas situações de cobertura (com e sem plástico transparente de 300 µm de espessura), dois estádios de desenvolvimento da planta daninha (vegetativo e florescimento) e três períodos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
1
0
3
Order By: Relevance
“…The effect of solarization on dry matter accumulation and density of the perennial Cyperus spp. confirms previous reports (Kuva et al, 1995). Under tropical conditions, Kumar et al (1993) also observed that solarization may reduce population of C. rotundus when emerged from seeds, but not when their flushes had been emerged from tubers.…”
Section: Resultssupporting
confidence: 88%
“…The effect of solarization on dry matter accumulation and density of the perennial Cyperus spp. confirms previous reports (Kuva et al, 1995). Under tropical conditions, Kumar et al (1993) also observed that solarization may reduce population of C. rotundus when emerged from seeds, but not when their flushes had been emerged from tubers.…”
Section: Resultssupporting
confidence: 88%
“…Contudo, observações a seu respeito são fundamentais, pois essa espécie apresenta-se com muita agressividade nas lavouras e é de difícil controle (KISSMANN & GROTH, 1997). Porém, o desenvolvimento da tiririca é afetado pelo sombreamento do solo, onde, nessa condição, é retardado o desenvolvimento normal das plantas (KUVA et al, 1995).…”
Section: Resultsunclassified
“…They used transparent polyethylene films to increase soil temperature to values as high as 42.5 C at .015 m depth. Kuva et al 37 have used transparent plastic films for controlling tiririca, or cocograss (Cyperus rotundus) by reaching an average soil temperature of 38.6 C at 0.10 m depth. They showed that plastic film coverage reduced infestation.…”
Section: Evaluatedmentioning
confidence: 99%